2020
DOI: 10.1371/journal.pone.0238028
|View full text |Cite
|
Sign up to set email alerts
|

Willingness to participate in future HIV vaccine trials among men who have sex with men and female sex workers living in Nairobi, Kenya

Abstract: Objective To evaluate factors associated with willingness to participate in future HIV vaccine trials among men who have sex with men and female sex workers living in Nairobi, Kenya. Background Working with 'key populations', those at elevated risk of HIV acquisition, is important to conduct efficient HIV prevention trials. In Nairobi Kenya, HIV infection is higher in men who have sex with men (MSM) and female sex workers (FSW) than in the general adult population, hence the need to establish if they would be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 21 publications
2
18
0
Order By: Relevance
“…We have previously reported results from this study demonstrating a high willingness to participate in HIV vaccine trials among members of these key populations from Nairobi, Kenya (14). Here, we report a high level of retention among study participants.…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…We have previously reported results from this study demonstrating a high willingness to participate in HIV vaccine trials among members of these key populations from Nairobi, Kenya (14). Here, we report a high level of retention among study participants.…”
Section: Discussionsupporting
confidence: 61%
“…An alcohol use disorder screening test, the CAGE (29) was administered. We evaluated HIV prevention knowledge to assess both biomedical and behavioural prevention methods at the last study visit (14).…”
Section: Follow Up and Volunteer Retentionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consistent with previous studies [ 7 ], we found that a fairly large proportion (36%) of participants LTFU did not attend any follow-up visit, or only attended one follow-up visit. This finding lends support to proposals for preparatory cohorts in which potential HIV prevention trial participants demonstrate availability for long-term follow-up and willingness to comply with the study visit schedules prior to enrolment [ 7 , 14 ].…”
Section: Discussionsupporting
confidence: 55%
“…A recent study in Kenya reported a desire to receive healthcare and information about HIV were the motivating factors to participate in an HIV vaccine trial among MSM and FSW 25 . Furthermore, a review of the literature reported that retention and sexual disinhibition were the main socio-behavioural challenges for HIV vaccine efficacy trials in Sub-Saharan Africa.…”
Section: Introductionmentioning
confidence: 99%